The Character of Student Learning Discipline at MI Muhammadiyah Karanganyar - Putri, Faradila Arfina; Muhroji, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to explore how the character of learning discipline is applied among students at MI Muhammadiyah Karanganyar and to identify the internal and external factors influencing its habituation as well as its impacts on student outcomes. Recognizing that disciplined learning habits are foundational for academic success yet often difficult for learners to maintain, the research investigates how discipline character is fostered across school, home, and tutoring environments. Methodology: Employing a descriptive qualitative design, data were collected through in‑depth interviews with students, teachers, and parents, alongside direct observations of classroom and study‑support settings. To ensure validity, the study applied both source triangulation—drawing insights from multiple stakeholder perspectives—and technique triangulation, combining verbal reports with observed behaviors. Data analysis followed an interactive model of coding, categorization, and thematic synthesis before drawing conclusions based on converging evidence. Results: The findings reveal that learning discipline is actively cultivated through structured class routines, consistent parental reinforcement at home, and guidance in tutoring sessions. Internally, students’ self‑motivation and sense of responsibility emerged as critical drivers of disciplined behavior, while externally, parental support and peer influences played reinforcing roles. Habitual discipline led to measurable improvements in students’ time‑management skills, increased accountability for tasks, and the creation of a more positive and focused learning environment. Applications/Originality/Value: By demonstrating that effective character habituation requires coordinated efforts among schools, families, and broader community contexts, this study underscores the importance of a holistic approach to character education. Its insights can inform school policies, parent‑engagement programs, and tutor‑training initiatives aimed at embedding discipline habits in learners, thereby better preparing them to face both academic challenges and life’s broader demands.